Homo Capax Dei: Kemampuan Penyandang Disabilitas Intelektual dalam Mengenal Allah - Magdalena, Emy (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract. The church has always been faced with the issue of serving people with intellectual disabilities. The question arises, whether people with intellectual disabilities are whole human beings who the Image of God (Imago Dei) are, which is traditionally understood as only related to the intellectual and rational dimensions. This study aimed to explore the divine ability (Capax Dei) of people with intellectual disabilities in acknowleging God. The research method used was literature study. The result of this study confirmed that people with intellectual disabilities have a unique way of building a relationship with the Creator. Divine ability cannot only be determined based on cognitive capacity and fluency in expressing one's spiritual condition.Abstrak. Gereja selalu berhadapan dengan isu pelayanan terhadap penyandang disabilitas intelektual. Muncul pertanyaan, apakah penyandang disabilitas intelektual adalah manusia seutuhnya yang merupakan Gambar Allah (Imago Dei), yang mana secara tradisional konsep tersebut dipahami hanya terkait dengan dimensi intelektual dan rasionalitas. Penelitian ini bertujuan untuk mengeksplorasi kemampuan ilahi (Capax Dei) penyandang disabilitas intelektual dalam mengenal Allah. Metode peneltian yang digunakan adalah studi literatur. Hasil kajian ini menegaskan bahwa penyandang disabilitas intelektual memiliki cara yang unik di dalam membangun relasi dengan Sang Pencipta. Kemampuan ilahi tidak bisa hanya ditentukan berdasarkan kapasitas kognitif dan kefasihan dalam mengekspresikan kondisi spiritualnya.